Singing patterns of the Oriental Magpie Robin Copsychus saularis Linn. - Karna, J.; Subba, B. R.; Bhattacharya, H.; Chhetry, D. T. (Our Nature, 2020)
Oriental Magpie Robin is a song bird that resides in some tropical regions of Asia. The present work was attempted to provide a detailed study of the territorial singing of this species in the area of Biratnagar (Nepal). Songs of Oriental Magpie Robin was recorded by using a digital voice recorder (Olympus VN-8700PC) for one hour without break at seven selected sites in Biratnagar. Recorded songs were converted in the form of spectrogram by using avisoft. Seven Oriental Magpie Robins, belonging to seven different study sites of Biratnagar were taken as subjects and have been abbreviated as Bird A, B, C, D, E, F and G respectively. It was very surprising that there was not even a single motif which was matching among any of the birds. Out of 1782 song samples recorded from seven individuals, 328 types of songs were identified. These songs were composed of 3 to 18 types of elements.